Scheduling nurse shifts based on their preferenceusing goal programming approach / Nurul Syazana Shaful Rasydy, Nurul Aqilah Badrud-Din and Nadhirah Mat Rosdi - Shaful Rasydy, Nurul Syazana; Badrud-Din, Nurul Aqilah; Mat Rosdi, Nadhirah (2022)
Nurse Scheduling Problem (NSP) is the process of assigning available nurses to predetermined shifts in order to satisfy hospital needs. NSP is incredibly difficult because it is time consuming and also need to satisfy all the hospital requirements and nurses preferences. Bad scheduling can lead to dissatisfaction and frustration among nurses which results in a stressful and demotivating work atmosphere. In this project, a computerised NSP is created using a Goal Programming (GP) model. This model is created to aid in Hospital Tuanku Fauziah (HTF) enhance their manual schedule construction. This hospital has several main planning goals in scheduling their nurses timetable which are converted to be hard and soft constraints of the GP model. This study is using hospital policies as hard constraints and nurses’ preference as soft constraints. The complete formulated goal programming model is then solved using the help of LINGO software. The final result shows that the timetable obtained from the GP model gives better schedule compared to manually constructed timetable. Furthermore, this study demonstrates that employing LINGO software to solve the formulated GP model improves nurse satisfaction.